Entrepreneurship in rural women of the 21st century - Antúnez Sánchez, Alcides (DIXI, 2019)
Objective: the enterprise has positioned itself inside universities as one of the important themes, considering that disciplinary training is not enough to act successfully today; in addition, it is necessary to build capacities and offer life alternatives for future professionals with skills in the 21st century. Governments also link entrepreneurship within their agendas and structure plans, programs and projects to strengthen it, understanding that its promotion can contribute to the countries’ economic and social development. This essay aims to demonstrate the need to promote public policies in universities in Latin America that tax the enterprise to train a professional with skills in his incursion into the role of business women in rural development.Methodology: for this, methods such as synthesis analysis, induction, deduction, history were used.Results: in recent years, the phenomenon of entrepreneurship has suddenly appeared in our societies as if it were a cultural movement. Actions, institutions, units and services that strive to support theentrepreneurial spirit have increased.Conclusions: it is a fact that universities are a fundamental part of the entrepreneurial and innovation ecosystems.
Keywords: quality; trainingtraining; promotion; pedagogical model